2011
DOI: 10.1002/ijc.26160
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations of a cell adhesion molecule CADM4 in renal clear cell carcinoma

Abstract: Renal clear cell carcinoma (RCCC) is the most frequent subpopulation of renal cell carcinoma and is derived from the proximal uriniferous tubules. We have previously reported that an actin‐binding protein, 4.1B/DAL‐1, is expressed in renal proximal tubules, whereas it is inactivated in 45% of RCCC by promoter methylation. In the lung and several epithelial tissues, 4.1B is shown to associate with a tumor suppressor protein, CADM1, belonging to the immunoglobulin‐superfamily cell adhesion molecules. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…The aforementioned breast cancer tissue samples were fixed in 10% formalin, embedded in paraffin, cut into 4 µm sections and stained with hematoxylin and eosin (H&E) and other primary antibodies. Rabbit polyclonal antibodies against CADM1 (1:500, C-18, generated by the Division of Molecular Pathology, Institute of Medical Science, The University of Tokyo) and CADM4 (1:500, Bc-2, generated by the Division of Molecular Pathology, Institute of Medical Science, The University of Tokyo) were used as described previously (20). Antibodies used for IHC staining were as follows: Anti-ER (1:500, cat.…”
Section: Introductionmentioning
confidence: 40%
“…The aforementioned breast cancer tissue samples were fixed in 10% formalin, embedded in paraffin, cut into 4 µm sections and stained with hematoxylin and eosin (H&E) and other primary antibodies. Rabbit polyclonal antibodies against CADM1 (1:500, C-18, generated by the Division of Molecular Pathology, Institute of Medical Science, The University of Tokyo) and CADM4 (1:500, Bc-2, generated by the Division of Molecular Pathology, Institute of Medical Science, The University of Tokyo) were used as described previously (20). Antibodies used for IHC staining were as follows: Anti-ER (1:500, cat.…”
Section: Introductionmentioning
confidence: 40%
“…To date, reduced expression and loss of CAMD4 has been studied in glioma, prostatic, renal and colon cancers 5 6 8 16. The correlation between CADM4 expression and clinicopathological factors has been investigated only in two cancers: renal cell carcinoma and colorectal adenocarcinoma 8 16.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between CADM4 expression and clinicopathological factors has been investigated only in two cancers: renal cell carcinoma and colorectal adenocarcinoma 8 16. Nagata et al 16 suggested that promoter methylation was involved in the silencing of CADM4 in renal cell carcinoma (human renal cancer 786-O cells). They demonstrated that loss of CADM4 expression occurred more frequently in renal cell carcinoma with vascular invasion than without it (p=0.04), which indicated a relationship between CADM4 and tumour invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Nagata et al 14 obtained evidence that promoter methylation is involved in the silencing of CADM4. When they treated human renal cancer 786-O cells (in which CADM4 expression is undetectable) with methyl transferase, they found that synthesis of CADM4 mRNA was restored.…”
Section: Discussionmentioning
confidence: 99%